The phonological structure of words : - Ewen, Colin J. (Cambridge University Press, 2001)
This book is designed to provide students of phonology with an accessible introduction to the phonological architecture of words. It offers a thorough discussion of the basic building blocks of phonology--in particular features, sounds, syllables and feet--and deals with a range of different theories about these units. The book provides a more detailed analysis of this subject than previously available in introductory textbooks and is an invaluable and indispensable first step toward understanding the major theoretical issues in modern phonology at the word level.